Integrasi Lingkungan Alam Sekitar Untuk Meningkatkan Calistung Pada Usia Sekolah Dasar Di Desa Tebing Tanjung Selamat, Kecamatan Padang Tualang, Kabupaten Langkat - Fatmawati, Fatmawati; Puspita, Dinda; Aulia, Dhini; Agid Pratama, Febriano; Saputra, Gunawan; Mustika, Nanda; Zannah, Nurul; Ayu Pratiwi, Novia; Irsani, Salsabila; Yusrizal, Yusrizal (PELITA NUSA TENGGARA, 2025)
The ability to read, write, and count (Calistung) is a fundamental skill that elementary school students must master as a foundation for further learning. In Tebing Tanjung Selamat Village, Padang Tualang Sub-district, Langkat Regency, students' Calistung proficiency remains low due to the lack of varied teaching methods and the underutilization of the surrounding natural environment as a learning resource. This Community Service Program (PKM) aims to improve students’ Calistung skills through the integration of the natural environment into the learning process. The program was implemented through teacher training, the development of contextual learning modules based on the local environment, and direct assistance during learning activities. The results of the program show a significant improvement in students' Calistung abilities, as indicated by the increase in average pre-test and post-test scores. Active participation from teachers, students, and the local community played a key role in the program’s success. In addition to improving students' basic competencies, the program produced valuable outputs such as learning modules and best practices that can be replicated in other rural areas with similar characteristics. Environment-based learning has proven to be effective, enjoyable, and relevant for enhancing students’ basic skills in rural settings.